The Preferred Governing Actors of Populist Supporters: Survey Evidence From Eight European Countries - Pilet, Jean-Benoit (2024)
Populist parties have been shown to attract many voters disillusioned with representative democracies. And some of these parties do indeed propose models of government that challenge contemporary democratic systems. However, we do not know exactly what the democratic preferences of populist party supporters are. We propose to fill this gap by investigating the types of actors that citizens who are more sympathetic to populist parties would like to see play a greater role in their national political system. First, we find that populists believe that citizens should be more involved, highlighting the people-centred nature of populism. Second, they advocate a greater role for business leaders, military generals, and religious leaders, a preference found among both right-wing and left-wing populists. Third, left-wing populists show a unique preference for scientific experts in government, suggesting a technocratic inclination. Conversely, right-wing populists are particularly critical of elected politicians, underlining their deep anti-elitist attitudes. Our findings suggest that, among citizens who are more sympathetic to populist parties, there is support for models of government that challenge representative democracy. The question is whether populist parties would be influenced by these citizens to push for institutional reforms.